PERANCANGAN UI/UX WEBSITE ARTHA BONSAI DENGAN TUJUAN MEMBANGUN BRAND AWARENESS - Bintang Pramudya Putra Prasetya; Sultan Arif Rahmadianto; Bayu Andika Putra (Sainsbertek Jurnal Ilmiah Sains & Teknologi, 2026)
Artha Bonsai, a bonsai business with over 35 years of experience and an export market, faces challenges in building global brand awareness due to the lack of an official website. This absence of a digital platform hinders new market reach and consistent brand identity communication. This research aims to design a User Interface (UI) and User Experience (UX) for the Artha Bonsai website capable of building brand awareness by representing the brand identity visually and functionally. The design method used is Design Thinking, which includes the empathize, define, ideate, prototype, and test stages. Data was collected through interviews, observation, surveys, and literature studies, then analyzed using SWOT analysis. The result of this design is a high-fidelity desktop version of the website prototype, which was tested on 10 users and a UI/UX expert. User testing results showed a very good acceptance level with an average score of 4.5 out of 5 , while the expert review provided professional validation and further development suggestions.